The Influence of Organizational Culture, Compensation, and Work Environment on Employee Performance in Class II B Bangko Correctional Institutions - Anggara Bratama; Erianjoni Erianjoni (Jurnal Ilmiah Ilmu Administrasi Publik, 2020)
ABSTRACTThis study aims to reveal the influence of organizational culture, compensation, and work environment on employee performance at the Bangko Class II Penitentiary, either directly or indirectly for Bangko Class II B Prison employees. This study uses a quantitative method, with exogenous variables, namely organizational culture (X1), compensation (X2), work environment intervening variables (X3) and endogenous variables, namely employee performance (Y) at Bangko Class II Correctional Institution (Lapas). The population of this research is all employees of Lapas in Bangko Class II Correctional Institution, namely 55 people. The sample was obtained through total sampling so that the respondents in this study amounted to 55 samples. The data analysis technique used is path analysis and is divided into 2 paths, namely sub-structure 1 and sub-structure 2. Data is collected through a questionnaire that has been validated and reliable in advance, both content and empirical test of items in the field. The results of this study have found that the hypothetical model is proven to be used as a new model in improving employee performance for every employee at the Bangko Class II Penitentiary.